Plant Size Plays an Important Role in Plant Responses to Low Water Availability and Defoliation in Two Woody Leguminosae Species - Wang, Ning; Li, Qiang; Liu, Xiao; Yi, Shijie; Zhao, Mingming; Sun, Xinke; Song, Huijia; Peng, Xiqiang; Fan, Peixian; Gao, Qun; Wang, Yongtao; Yu, Linqian; et al. (Frontiers in Plant Science, 2021)
.Plant size influences plant responses to combined environmental factors under climate change. However, their roles in plant ecophysiological responses are not fully understood. Two rapidly growing Leguminosae species (Robinia pseudoacacia and Amorpha fruticosa) were used to examine plant responses to combined drought and defoliation treatments (two levels of both treatments). Both 1.5-month-old seedlings and 3-month-old seedlings were grown in a greenhouse, and seedling growth, leaf gas exchanges, stem hydraulics and concentrations of non-structural carbohydrates were determined after 60 days of treatment. Our results indicated defoliation had no significant effect on plant height, basal diameter, and total biomass whatever plant sizes and species. Under the low water availability treatment, the defoliated seedlings significantly increased by 24% in stem water potential compared with non-defoliated seedlings in large R. pseudoacacia. Compared with the high water availability in large non-defoliated R. pseudoacacia seedlings, the low water availability significantly reduced by 26% in stem starch concentration to maintain the stem soluble sugar concentration stable, but not in small R. pseudoacacia seedlings. We also found a negative correlation between leaf and root soluble sugar concentration under low water availability in A. fruticosa. The results demonstrate defoliation could relieve the effect of low water availability in large seedlings. Large seedlings had more compensatory mechanisms in response to defoliation and drought treatments than small seedlings, thus species with large carbon reserves are more recommended for vegetation restoration under combined drought and defoliation conditions. Future studies with more species are crucial for obtaining more rigorous conclusions.